When I was researching on imaginary numbers, I came across this proof -

\(i=\sqrt { -1 } =\sqrt { -\frac { 1 }{ 1 } } =\frac { \sqrt { 1 } }{ \sqrt { -1 } } =\frac { 1 }{ i } =-i\)

which is clearly wrong. But even after analyzing it carefully, I couldn't find the error in it.

Where exactly is the error in the proof?

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestwait how is 1/i equal to negative i?

Log in to reply

Multiple 1/i by i/i

Log in to reply

root(a/b) = roota/rootb

only for positive numbers

Log in to reply

For complex numbers (unlike non-negative real numbers) the square root is defined as a multi-values function: \(\sqrt{-1}=\pm{i}\). If \(z\) is any non-zero complex number, then \(\sqrt{z}\) has two values.

Does that help?

Log in to reply

wait so if you take -1 and raise it to the 3/2 power, it would be i and -i? because -1^3/2 = (/sqrt{-1})^3/2 = /sqrt{-1} * /sqrt{-1} * /sqrt{-1} = -1 * /sqrt{-1} = -i, but it can't be i...

Log in to reply

Again, \((-1)^{3/2}=\pm{i}\) , with the "principal value" being \(-i\).

Log in to reply